The E3 ubiquitin ligase Itch deficiency promotes antigen‐driven B‐cell responses in mice. Issue 1 (20th July 2020) - Fang, Ying; He, Youdi; Zhai, Bing; Hou, Chunmei; Xu, Ruonan; Xing, Chen; Wang, Xiaoqian; Ma, Ning; Han, Gencheng; Wang, Renxi
Abstract: Deficiency of Itch, an E3 ubiquitin ligase, usually induced severe systemic and progressive autoimmune disease. The Itch function is well studied in T cells but not in B cells. We hypothesize that B‐cell‐specific Itch deficiency promoted antigen‐induced B‐cell activation and antibody‐expressing plasma cell (PC) production. We found that unlike Itch KO, Itch cKO (CD19 cre Itch f/f ) mice did not demonstrated a significant increase in the sizes of spleens and LNs, antibody level, and base mutation of antibody gene. However, in line with the fact that Itch expression decreased in GC B cells, PCs, and plasmablast (PB)‐like SP 2/0 cells, Itch deficiency promoted B‐cell activation and antibody production induced by antigens including lipopolysaccharide (LPS) and sheep red blood cells (SRBCs). Mechanistically, we found that Itch deficiency promotes antigen‐induced cytokine production because Itch controls the proteins (e.g., eIF3a, eIF3c, eIF3h) with translation initiation factor activity. Altogether, our data suggest that Itch deficiency promotes antigen‐driven B‐cell response. This may provide hints for Itch‐targeted treatment of patients with autoimmune disease. Abstract : Itch deficiency promoted antigen‐induced B‐cell activation and antibody production. Mechanistically, Itch deficiency promotes antigen‐induced cytokine production via translation initiation factors, for example, eIF3a, eIF3c, and eIF3h activity. This may provide some hints for Itch‐targeted treatment of patients with autoimmune disease.